PERAN MOTIVASI DALAM MEMEDIASI PENGARUH SISTEM REWARD TERHADAP KINERJA PEGAWAI - de Araujo, Florbela Monica; Sintaasih, Desak Ketut; Riana, I Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.08.NO.01.TAHUN 2019, 2018)
The objective of this study is to know about the effect of the reward system on the motivation, the effect of motivation on employee performance, the reward systems influence on employee performance, and to know the role of motivation in mediating the effect reward systems on performance employees. The population in this study were all employees work on the Direcção Nacional de Edificação Ministério das Obras Públicas in Dili,Timor-Leste, taken by census or saturated sampling, with a sample size of 41 employees, the research instrument was aquestionnaire and the technique of analysis techniques used namely Partial Least Square (PLS). The results of the study showed that the reward systems effect positively and significant on motivation, motivation effect positively and significant employee performance, the reward systems effect positively but not significant employee performance, the mediating role of motivation in effect reward systems on employee performance proven full mediation. Result of the research implied that reward systems effect on performance but it is not proven, however, is mediated by motivation can improve employee performance. This finding proved that motivation fully mediates the effect of reward systems on employee performance.